Concentration and periodicity in the control of the growth and development of the child under one year - Borneo Cantalicio, Eler (2019)
Objective. Analyze the relationship between the concentration and the periodicity of the control and the growth and development profile of the child under one year. Methods. A correlational design study was carried out with 309 children under one year from the Aparicio Pomares - Huanuco health center, in 2018. A data collection sheet was used. In the inferential analysis, the Pearson Chi-Square7 Test was used. Results. Among the newborns, 74.2% (207) presented a concentration of controls and 43.0% (120) maintained the periodicity of controls. Likewise, 94.3% (263) were diagnosed with adequate growth and 100.0% (279) had normal psychomotor development. In children aged 1 to 11 months, 62.8% (194) showed a concentration of controls and 13.9% (43) had a periodicity of controls. Similarly, 57.0% (176) were diagnosed with adequate growth and 97.7 % (302) had normal psychomotor development. On the other hand, the concentration of controls is related to the growth of newborns, with a p <= 0.004; while in children under one year of age, the concentration of controls is related to growth (p <= 0.003) and psychomotor development (p <= 0.014). Conclusions. The concentration of controls is significantly related to the growth and development of children under one year of the Aparicio Pomares - Huánuco health center.